Achieving Competitive Advantage by Using Supply Chain Strategies - Aram Hanna Massoudi (International Journal of Supply Chain Management, 2018)
The subject of the supply chain has received significant attention by researchers in the theoretical and applied fields of Operations Management and Marketing Management. Resulting in the need to develop successful strategies of supply chain and complement the organization's strategy in order to achieve competitive advantage. From this point view, the research problem was identified by asking questions about the strategies of supply chain and its suitability to the Company studied, as well as the knowledge of the requirements for successful supply chain, also knowing the effect of these strategies in achieving competitive advantage to the plant under study. The main objective of this research is to identify the relationship between supply chain strategies and competitive advantage in Alsamah Hosiery Company, Syria. The research used the null hypothesis to determine the relation and effect between the study variables which is strategies of supply chain and the dimensions of competitive advantage. The result showed that supply chain is part of a value chain that deals with key activities in the company, also supply chain strategies has an impact on the companys competitive advantage. The external supply strategy had the highest impact. A number of recommendations have been put forward to the factory studied, most importantly, the need to build long-term relationships with suppliers and trend towards establishing a partnership as well as the need to adopt competitive standards by the factory management in the selection of suppliers (cost, quality, and fast delivery). Keywords: Supply chain, Vertical integration strategy, External supply strategy, Competitive advantage.